Nutritional Status Screening and Hand Hygiene Health Education for Toddlers at Imanda Bandung Preschool Play Group - Nirmala, Sefita Aryuti; Suhartini, Linda; Ulya, Siti Nihlatul; Putri, Shici Hamaira; Alwi, Louis Angel; Izzaty, Mafaza (CV Media Inti Teknologi, 2025)
According to WHO, UNICEF, and the World Bank in 2021, stunting is the most common type of malnutrition among toddlers, namely 144 million stunted toddlers in the world and 53% are in Asia. 2018 Basic Health Research Report, West Java, the reason for not weighing children aged 0 – 59 months in the last 12 months was because parents were busy (26.2%) and forgot and/or didn't know their schedule (18.3%). Referring to this phenomenon, it is important to carry out height and weight checks at school. The community service activities carried out by Universitas Padjadjaran Midwifery Program and The Garuda Community Health Center aim to assess nutritional status and enhance toddlers' knowledge of proper hand-washing techniques at The Imanda Bandung Preschool Play Group. A total of ninety-nine toddlers had their height and weight measured at Imanda Bandung Preschool Play Group. The data obtained was analyzed using the WHO recommended z-scoore chart based on age and gender. Of the ninety-nine toddlers aged under five years 28.28% and aged over five years 71.72%. Ages under five years old have a normal nutritional status of 82.15%. Ages over five years have normal nutrition 67.60%, malnutrition 5.63%, and obesity 5.63%. Children with poor nutritional status and obesity are referred. Hand washing health education was followed by toddlers enthusiastically. Monitoring children's growth and development tends to decrease with age, leading to a lack of early detection of nutritional problems. Routine height and weight checks, including at school, are very important to determine a child's nutritional status.